Nutrition Adequacy Level and Stunting in Children Aged 48‒59 Months in the Coastal Area of Kendari City, Indonesia - Jufri, Nurnashriana; Marliyati, Sri Anna; Anwar, Faisal; Ekayanti, Ikeu (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
This study aims to explore the relationship between nutritional adequacy and height-for-age z-scores (HAZ) in toddlers in Kendari City's coastal region. This cross-sectional analysis involved 96 children aged 48‒59 months. Height measurements was converted to HAZ, while a 24-hour dietary recall was conducted to assess nutritional intake. Data were analyzed using Pearson product moment test and multiple linear regressions. The study revealed a significant HAZ correlation with calcium, iron, and copper adequacy levels (p<0.05). Notably, in Kendari City's coastal area, stunting is found in toddlers aged 48‒59 months due to nutritional inadequacy.